Public participation in healthcare students' education: An umbrella review - Lorelli Nowell; Bryn Keogh; Eleftheria Laios; Lisa Mckendrick‐Calder; Whitney Lucas Molitor; Kerry Wilbur (Health Expectations, 2024)
Abstract Background An often‐hidden element in healthcare students' education is the pedagogy of public involvement, yet public participation can result in deep learning for students with positive impacts on the public who participate. Objective This article aimed to synthesize published literature reviews that described the impact of public participation in healthcare students' education. Search Strategy We searched MEDLINE, EMBASE, ERIC, PsychINFO, CINAHL, PubMed, JBI Database of Systematic Reviews and Implementation Reports, the Cochrane Database of Systematic Reviews, Database of Abstracts of Reviews of Effects and the PROSPERO register for literature reviews on public participation in healthcare students' education. Inclusion Criteria Reviews published in the last 10 years were included if they described patient or public participation in healthcare students' education and reported the impacts on students, the public, curricula or healthcare systems. Data Extraction and Synthesis Data were extracted using a predesigned data extraction form and narratively synthesized. Main Results Twenty reviews met our inclusion criteria reporting on outcomes related to students, the public, curriculum and future professional practice. Discussion and Conclusion Our findings raise awareness of the benefits and challenges of public participation in healthcare students' education and may inform future research exploring how public participation can best be utilized in higher education. Patient or Public Contribution This review was inspired by conversations with public healthcare consumers who saw value in public participation in healthcare students' education. Studies included involved public participants, providing a deeper understanding of the impacts of public participation in healthcare students' education.